Studies on the Preparation, Characterization and Solubility of Nimodipine Inclusion Complexes with Β-Cyclodextrin - SK.MAJAHAR; R.M.RAO KUSUMANCHI; B.N.GAYATRI (International Journal of Pharma and Bio Sciences, 2010)
Nimodipine, a calcium channel blocker, is a highly crystlline powder which is practically insoluble in water, in aqueous fluids both acidic and alkaline. Because of its limited aqueous solubility it exhibits poor dissolution characteristics and its oral absorption is dissolution rate limited. In this study the effect of βcyclodextrin (βCD) on the aqueous solubility and dissolution rate of nimodipine was investigated. Phase solubility profiles indicated that the solubility of nimodipine was significantly increased in the presence of β-cyclodextrin and was classified as AL-type, indicating the formation of 1:1 stoichiometric inclusion complexes with a stability constant of 572 M-1. Solid complexes prepared by kneading method were characterized using differential scanning calorimetry and powder X-ray diffractometry. In vitro studies showed that the solubility and dissolution rate of nimodipine significantly improved by complexation with β-cyclodextrin with respect to the drug alone and lends an ample credence for better therapeutic efficacy.